2008
DOI: 10.1037/1076-898x.14.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Correcting distance estimates by interacting with immersive virtual environments: Effects of task and available sensory information.

Abstract: The tendency to underestimate egocentric distances in immersive virtual environments (VEs) is not well understood. However, previous research (A. R. Richardson & D. Waller, 2007) has demonstrated that a brief period of interaction with the VE prior to making distance judgments can effectively eliminate subsequent underestimation. Here the authors examine the mechanism underlying the effect of VE interaction and the conditions that may give rise to it. In Experiment 1, after interacting with an immersive VE, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
130
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 48 publications
10
130
2
Order By: Relevance
“…Concerning the Egocentric Distance Estimation Task (which consisted in evaluating the total distance travelled during the learning path phase), the results showed a significant difference for Input Devices, in favor of the Treadmill (vestibular information present) compared to the Joystick (i.e., no vestibular information because no head movements). These results are in accordance with different authors [11][12] who demonstrated that vestibular information is important to correctly estimate distances. An effect Rotation was also found, showing a distance overestimation for the conditions with Controlled Rotation compared to the conditions with Automatic Rotation.…”
Section: Egocentric Taskssupporting
confidence: 82%
See 3 more Smart Citations
“…Concerning the Egocentric Distance Estimation Task (which consisted in evaluating the total distance travelled during the learning path phase), the results showed a significant difference for Input Devices, in favor of the Treadmill (vestibular information present) compared to the Joystick (i.e., no vestibular information because no head movements). These results are in accordance with different authors [11][12] who demonstrated that vestibular information is important to correctly estimate distances. An effect Rotation was also found, showing a distance overestimation for the conditions with Controlled Rotation compared to the conditions with Automatic Rotation.…”
Section: Egocentric Taskssupporting
confidence: 82%
“…However, most of the studies agree that the extent of body-based information provided by a treadmill locomotion interface (compared to a joystick) was considered largely favorable for spatial learning in a VE [11][13] [14], due to the improvement in egocentric [11] and allocentric spatial representation [14], as well as navigational measurements [19]. Recently, Ruddle et al [14] assessed the role of both translational and rotational vestibular information on survey knowledge, using different locomotion interfaces (translational displacements with walking or treadmill Vs. no translational displacements with joystick), sometimes with the possibility of really turning the head (i.e., rotational vestibular condition or not) during rotational movement.…”
Section: Spatial Cognition Interfaces and Rotational Movements In Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one major hindrance to the usefulness of VEs is the tendency for viewers to underperceive depth extents, sometimes by as much as 50 % of the intended depth (e.g., Waller & Richardson, 2008). Underperception of depth characterizes judgments from oneself to an object (egocentric distance judgments; Loomis & Knapp, 2003) and also judgments of the distance between two objects separated in depth (exocentric distance judgments in the depth plane; Geuss, Stefanucci, Creem-Regehr, & Thompson, 2012).…”
mentioning
confidence: 99%